The Influence of Live Streaming, Flash Sales, and Online Customer Reviews on Generation Z's Purchasing Decisions on the TikTok Shop Platform in Sumbawa Regency - Jahmat; Irawati (Takaza Innovatix Labs Ltd., 2026)
The rapid growth of social commerce platforms like TikTok Shop has transformed Generation Z's shopping habits in rural areas such as Sumbawa Regency, where digital infrastructure challenges persist. Features including live streaming, flash sales, and online customer reviews drive interactive and urgent buying experiences amid rising e-commerce adoption in Indonesia. This study aims to examine the influence of these factors on Generation Z's purchasing decisions on TikTok Shop.This quantitative research employed purposive sampling to select 100 Generation Z respondents (aged 13-27) from Sumbawa Regency who had purchased on the platform. Data were gathered via online questionnaires using Google Forms, with analysis conducted through classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination via SPSS software.​Results reveal that live streaming (β=0.490, t=4.285, p=0.000), flash sales (β=0.540, t=3.903, p=0.000), and online customer reviews (β=0.178, t=2.206, p=0.030) positively and significantly affect purchasing decisions partially and simultaneously (F=51.461, p=0.000), explaining 60.6% of variance (Adjusted R²=0.606). Live streaming emerged dominant.In conclusion, TikTok Shop's marketing features significantly shape rural Generation Z buying behavior, urging optimized strategies for similar contexts.